The FLE Classroom: Between Observation and Reality (Case of the M’sila Region) - Gaoudi, Fella (El Omda in Linguistics and Discourse Analysis, 2022)
This small research is a testimony to the reality of the status of FLE (French as a Foreign Language) within our region (M’sila), which risks being obscured amid various concepts attempting to define bilingualism and a bilingual speaker. Our problem does not focus on definition itself, but rather seeks to examine the reality of its existence in our region (we are, of course, referring to the teaching of FLE). That said, the body of this work is presented as a conclusion drawn from a professional experience. Our sample is therefore diverse (middle school, high school, and university). The study adopts a free-form writing approach, followed by an analysis of some results obtained from our informants and from about ten teachers.